PENGARUH PERTUMBUHAN PERUSAHAAN, STRUKTUR MODAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Nurfadilah, Siti; hasanah, neneng (Publika Citra Media, 2025)
This research aims to examine the influence of company growth, capital structure and corporate social responsibility on firm value in energy sector mining companies listed on the Indonesia Stock Exchange in 2019-2023. The population in this study was 87 companies with the observation year 2019-2023. The sample selection in this study used purposive sampling technique. The number of samples obtained was 11 companies with 5 years of research, so that 55 observation data were obtained. The data analysis technique used is multiple regression analysis using e-views version 12 software. The results of the research show that the variables Company Growth, Capital Structure and Corporate Social Responsibility simultaneously influence Firm Value. Partial company growth has no effect on firm value. Capital Structure has a significant effect on Firm Value. Corporate Social Responsibility has no effect on Firm Value.